Dietary Supplements as Supportive Therapy in Endometriosis: A Systematic Review - Szczotka, Dominika; Szafraniec, Artur; Krężel, Maciej; Krężel, Olga (Journal of Education, Health and Sport, 2026)
Endometriosis is a chronic, inflammatory gynecological disorder affecting 10–15% of women of reproductive age, characterized by ectopic endometrial tissue, dysmenorrhea, dyspareunia, chronic pelvic pain, and infertility. Its pathophysiology involves a complex interplay of inflammation, oxidative stress, angiogenesis, and dysregulated apoptosis. Conventional management strategies, including hormonal therapies and surgical interventions, are often limited by recurrence, side effects, and incomplete symptom relief. Consequently, interest has grown in adjunctive approaches, particularly dietary supplementation, for symptom management. Current evidence suggests that dietary supplementation may offer therapeutic benefit in endometriosis through anti-inflammatory, antioxidant, immunomodulatory, and antiproliferative mechanisms. While promising, these interventions should be considered adjunctive to standard medical or surgical treatment. Larger, well-designed clinical trials are needed to validate efficacy, establish optimal dosing, and determine long-term safety of supplementation strategies in endometriosis management.